Caracterización fisicoquímica y microbiológica de un concentrado proteico fermentado a partir del suero de quesería - Campoverde Jumbo, Vanessa Rosario (2023)
Cheese whey is the by-product resulting from cheese making, which contains a large amount of nutrients that can be used for the development of new products, thus avoiding causing damage to the environment by being discarded directly to the earth's surface or Water. The purpose of this research is to use cheese whey from the dairy industry for the preparation and characterization of a protein concentrate fermented with Lactobacillus plantarum. For this, we worked with the base formula of the company Productos Alimenticios “San Salvador” and a physicochemical test was applied to the resulting product that was interpreted through an exploratory data analysis and the microbiological stability was determined on days 1, 15 and 30 storage at room temperature. It was found that this fermented protein concentrate has a fat content of 2.32%, ash 1.90%, fiber 1.06%, carbohydrates 29.67% and protein 29.8%. Finally, with the microbiological analysis it was determined that the useful life of the product is approximately 30 days, under the conditions presented in this study. It is concluded that the fermented protein concentrate can be considered as an ingredient of high nutritional and probiotic value to enrich the nutrition of animals or for the human diet, however, research must continue to guarantee its effectiveness